Lack of cytotoxic and genotoxic effects of Minthostachys verticillata essential oil: Studies in vitro and in vivo - Escobar, Franco Matias (2012)
Minthostachys verticillata (peperina) is an aromatic and medicinal plant with several uses and ethnobotanical properties. Numerous studies have demonstrated that its essential oil (Mv-EO) presents antimicrobial capacity and shows immunomodulating and anti-allergic properties in human cell lines. Thus, the goal of this study was to investigate the main chemical composition, analyzed by GC?FID, and the cyto-genotoxic effects of Mv-EO, using Vero cells, human PBMCs and mice bone marrow cells. The Mv-EO was rich in pulegone 60.5% and menthone 18.2%. Our results clearly show that Mv-EO is not cyto-genotoxic in vitro nor in vivo. It not induced cytotoxic effects, as indicated by trypan blue dye exclusion and NRU assays both in Vero cells and human PBMCs. In addition, Mv-EO (100?1000 μg/mL) not induced apoptotic effects on human PBMCs, as indicated by Hoechst staining and DNA fragmentation analysis by agarose gel electrophoresis. The in vivo assay showed that Mv-EO (25?500 mg/kg) not increased the frequency of micronucleus in bone marrow cells of mice. Further, the ratio of polychromatic/normochromatic erythrocytes was not modified. These findings suggest that Mv-EO appears to be safe as a therapeutic agent.